The Relationship between Family Knowledge, Attitudes and Perceptions with Mothers' Compliance with Basic Immunization for Babies 0-12 Months in Sukamandijaya Village, Ciasem District, Subang Regency - Meilani Allisya (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Immunization is one of the essential public health efforts that is effective in providing specific immunity against diseases that can be prevented by immunization (PD3I). Ciasem District, Subang Regency, where Complete Basic Immunization (IDL) coverage in 2023 is 77.8%, there has been a decrease compared to 2020 which reached 87.8%. Several causal factors include knowledge, attitudes and family perceptions. The aim is to determine the relationship between knowledge, attitudes and perceptions of families with mothers' compliance with basic immunization for babies 0-12 months in Sukamandijaya Village, Ciasem District, Subang Regency. The method used is quantitative analysis with a cross sectional design. The community service sample was 92 mothers who had babies aged 13-24 months using a purposive sampling technique. The community service instrument used a questionnaire. The data is primary data analyzed using the chi square test. Univariate analysis revealed that the majority of mothers complied with basic immunization for babies aged 0-12 months as much as 73.9%, had good knowledge 70.7%, positive attitudes 62.9% and positive perceptions 64.1%. The results of the bivariate analysis showed a relationship between knowledge (p value = 0.001), attitude (p value = 0.000) and family perception (p value = 0.000) with maternal compliance with basic immunization for babies 0-12 months. The conclusion is that there is a relationship between family knowledge, attitudes and perceptions and maternal compliance with basic immunization for babies 0-12 months.